Measuring the effect of Choosing Wisely: an integrated framework to assess campaign impact on low-value care. Issue 8 (19th June 2015) - Bhatia, R Sacha; Levinson, Wendy; Shortt, Samuel; Pendrith, Ciara; Fric-Shamji, Elana; Kallewaard, Marjon; Peul, Wilco; Veillard, Jeremy; Elshaug, Adam; Forde, Ian; Kerr, Eve A
Abstract : The Choosing Wisely campaign began in the USA in 2012 to encourage physicians and patients to discuss inappropriate and potentially harmful tests, treatments and procedures. Since its inception, the campaign has grown substantially and has been adopted by 12 countries around the world. Of great interest to countries implementing the campaign, is the effectiveness of Choosing Wisely to reduce overutilisation. This article presents an integrated measurement framework that may be used to assess the impact of a Choosing Wisely campaign on physician and provider awareness and attitudes on low-value care, provider practice behaviour and overuse of low-value services.